2012
DOI: 10.5802/aif.2717
|View full text |Cite
|
Sign up to set email alerts
|

Three-manifolds and Kähler groups

Abstract: ABSTRACT. We give a simple proof of a result originally due to Dimca and Suciu [6]: a group that is both Kähler and the fundamental group of a closed three-manifold is finite. We also prove that a group that is both the fundamental group of a closed three-manifold and of a non-Kähler compact complex surface is Z or Z ⊕ Z 2 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The proof of Theorem 2 given above has the pleasant feature of dealing with the cases that M is closed or with non-empty boundary uniformly. In particular, it gives yet another treatment of closed three-manifolds that is different from [4,12]. Now, taking for granted the closed case, an alternative -and much more high-tech -treatment of manifolds with non-empty and non-spherical boundary is implicit in my recent paper [13], where I discussed Kähler groups of positive deficiency.…”
Section: Primenessmentioning
confidence: 99%
“…The proof of Theorem 2 given above has the pleasant feature of dealing with the cases that M is closed or with non-empty boundary uniformly. In particular, it gives yet another treatment of closed three-manifolds that is different from [4,12]. Now, taking for granted the closed case, an alternative -and much more high-tech -treatment of manifolds with non-empty and non-spherical boundary is implicit in my recent paper [13], where I discussed Kähler groups of positive deficiency.…”
Section: Primenessmentioning
confidence: 99%
“…While a general answer seems out of reach for the moment, it is fruitful to consider Serre's question in the context of more specific classes of groups. For instance, it has been shown that if the fundamental group of a compact 3-manifold without boundary is Kähler then it is finite [20] (see also [6] and [26]) and that a Kähler group with non-trivial first L2-Betti number is commensurable to a surface group (i.e. the fundamental group of a closed Riemann surface) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Remark 3.12. In order to recover the main Theorems of [DiSu] or [Ko1] from Theorem 3.4 with the modifications mentioned in Remark 3.11, it remains to show that fundamental groups of circle bundles N over closed surfaces of positive genus are not Kähler. If the bundle is trivial, then b 1 (N ) is odd.…”
Section: The Next Proposition Addresses Casesmentioning
confidence: 99%
“…A group is called quasiprojective (respectively, Kähler) if it is the fundamental group of a smooth complex quasiprojective variety (respectively, compact Kähler manifold). Kähler and quasiprojective 3manifold groups have attracted much attention of late [DiSu,Ko1,BMS,DPS,FrSu,Ko2]. In this paper we characterize quasiprojective 3-manifold groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation